Factors Associated with Knowledge of Third Trimester Pregnant Women About Benefits of Giving Colostrum to Newborns Baby - Siregar, Rohani (Jurnal MIDPRO, 2023)
Colostrum is the first milk that comes out on the first day until the third day after the baby is born. Colostrum is produced from the 16th week of pregnancy (lactogenesis). One way to reduce AKN and IMR is to improve nutrition early in life and can affect quality of life. Community nutrition improvement activities are the percentage of newborns receiving colostrum through early breastfeeding initiation (IMD). The results of a preliminary study conducted on 8 mothers who had babies, obtained 6 mothers who did not know about colostrum and its benefits, and had never given breast milk to their babies for the first time, and the milk was thrown away, because they thought breast milk was stale. Meanwhile, 4 mothers gave the first breast milk to their babies through early initiation of breastfeeding. The purpose of this study was to determine the factors related to the knowledge of third trimester pregnant women about the benefits of colostrum in newborns in Karangraharja village. This type of research is a quantitative survey, and data collection was carried out in a cross sectional manner. The population in this study were all third trimester pregnant women in Karangraharja village. The sample of this research is the total population with a sample of 83 respondents. This primary data was collected by distributing questionnaires. The statistical analysis used is the frequency distribution, chi square and logistic regression. The results showed that 50.6% of respondents had less knowledge about giving colostrum to newborns. Variables that are significantly related are age with pvalue=0.009, education with pvalue=0.014, parity with pvalue=0.035, family support with pvalue=0.031, support for health workers with pvalue=0.037 The dominant variable is Age OR value 3.431 means age â‰¥ 35 have a 3.4 times chance of having good knowledge about colostrum compared to the age of 20-35 years, it is concluded that age can affect one's comprehension and mindset. The older you are, the more your comprehension and mindset will develop, so that the knowledge gain will improveÂ